Dr. Vivian Pinn: a woman pioneer & leader - Gloria Bachmann; Nancy Woods (BMC, 2021)
Abstract The Women's Health Institute in collaboration with the Journal of Women's Midlife Health hosted a national roundtable with Dr. Vivian Pinn via Zoom to honor her for her achievements in the areas of women's health, wellness, and research. The panelists included Gloria A. Bachmann, MD, MMS, Sherri-Ann Burnett-Bowie, MD, MPH, and Sioban D. Harlow, PhD.